PENGARUH HARGA EMAS DUNIA, INFLASI DOMESTIK DAN KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN SUB-SEKTOR PERTAMBANGAN EMAS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2024-2025 - Lusiana Lusiana; Winny Lian Seventeen; Fathul Hilal Perdana Kusuma (Universitas Muhammadiyah Bengkulu, 2026)
This study aims to analyze the influence of world gold prices, domestic inflation, and financial performance proxied by Return on Equity (ROE) and Net Profit Margin (NPM) on the stock prices of gold mining sub-sector companies listed on the Indonesia Stock Exchange for the period 2024–2025. The research method used is a quantitative method with a descriptive and associative approach. The research sample consisted of 5 companies selected using a purposive sampling technique with a total of 105 observations during the period January 2024 to September 2025. Data analysis was carried out using multiple linear regression with the help of SPSS version 26 through the classical assumption test, t-test, F-test, correlation analysis, and coefficient of determination. The results show that world gold prices have a positive and significant effect on stock prices, domestic inflation does not have a significant effect on stock prices, ROE does not have a significant effect on stock prices, while NPM has a negative and significant effect on stock prices and is the most dominant variable. Simultaneously, world gold prices, domestic inflation, ROE, and NPM have a significant effect on stock prices with a coefficient of determination of 39.4%. The conclusion of this study is that world gold prices and NPM are the main factors influencing the share prices of gold mining sub-sector companies, while domestic inflation and ROE have not been able to provide a significant influence during the research period. Keywords: World Gold Price, Domestic Inflation, Return on Equity, Net Profit Margin, Stock Price